Who Backs Separation? An Empirical Assessment of the Objective and Subjective Markers of Identity in Support for Secession in Catalonia. Issue 2 (14th August 2021) - Guinjoan, Marc
Abstract: Objective markers of distinctiveness such as language, ethnicity, religion, or origin are instrumental in the formation of territorial identities. In turn, territorial identity tends to be the most powerful factor in explaining differences in support for secession. Along with this subjective identity, objective markers of distinctiveness also play a role in explaining support for secession. In this article, I argue that the literature lacks an empirical assessment of how objective and subjective markers of identity are related to support for secession. In particular, I argue that most of the effect of objective markers on support for secession is indirectly expressed via (changes in) identity. Results from survey data from Catalonia (2015–2020, N = 30, 000), confirm that a large share of the effect of the region's objective markers—language and ancestry—on secession is, as expected, mediated. This evidence has both theoretical and empirical implications for studies on identity formation and support for secession.